The Duration of Employment Opportunities in U.S. Manufacturing - Dunne, Timothy; Roberts, Mark J. (The Review of Economics and Statistics, 1991)
Long-duration employment opportunities are a necessary condition for workers to hold lifetime jobs. This paper uses longitudinal data on individual U.S. manufacturing plants from 1963-1982 to estimate the age and completed spell distributions for employment positions. The results indicate that, of the employment opportunities in progress in the U.S. manufacturing sector in 1982, 30.0% were at least 19 years old and 59.6% would have a completed length of at least 20 years. High rates of turnover in employment positions coexist with a large number of long-duration employment opportunities because the turnover tends to be concentrated within a subset of the producers. Copyright 1991 by MIT Press.